A study on effect of gender differences and marital status towards organizational commitment in Syarikat Air Johor (SAJ) Holdings, Muar / Nur Nadiah Omar and Fatin Anisa Wahid - Omar, Nur Nadiah; Wahid, Fatin Anisa (Faculty of Business and Management, 2015)
This research is being done with the purpose to study the effects of gender differences and marital status on organizational commitment (affective, continuance and normative) in Syarikat Air Johor Holdings Muar. This study involved 139 respondents that consist of non-executive employees of SAJ at Muar branch. The data are gathered and analyzed by using the Statistical Package for Social Science (SPSS) Version 20. The result from the study shows that gender differences and marital status do have a significant difference with employees’ normative commitment. Besides, it also found that the level of commitment of the employees is in moderate level.